Fueling the development of elderly care services in China with digital technology: A provincial panel data analysis - Jiaxin He; Dangchen Sui; Lingpeng Li; Xinyan Lv (Heliyon)
Background: The global demographic shift towards an aging population presents significant challenges to elderly care cervices, which encompass the range of services designed to meet the health and social needs of older adults. Particularly in China, the aging society's diverse needs are often met with service inadequacies and inefficient resource allocation within the elderly care cervices framework. Objective: This study aims to investigate the transformative potential of digital technology, which includes innovations such as e-commerce, cloud computing, and artificial intelligence, on elderly care cervices in China. The objective is to assess the impact of digital technology on service quality, resource allocation, and operational efficiency within the elderly care cervices domain. Methods: Employing Stata software, the study conducts an analysis of panel data from 30 Chinese provinces over the period from 2014 to 2021, examining the integration and application of digital technology within elderly care cervices to identify trends and correlations. Results: The findings reveal that the integration of digital technology significantly enhances elderly care cervices, improving resource allocation and personalizing care, which in turn boosts the quality of life for the elderly. Specifically, a one-percentage point increase in the development and adoption of digital technology within elderly care cervices is associated with a 21.5 percentage point increase in care quality. Conclusion: This research underscores the pivotal role of digital technology in revolutionizing elderly care cervices. The findings offer a strategic guide for policymakers and stakeholders to effectively harness digital technology, addressing the challenges posed by an aging society and enhancing the efficiency and accessibility of elderly care cervices in China. The application of digital technology in elderly care cervices is set to become a cornerstone in the future of elderly care, ensuring that the needs of the aging population are met with innovative and compassionate solutions.